+0  
 
0
305
1
avatar

Let $f(x)=x+2$ and $g(x)=x/3.$ Also denote the inverses to these functions as $f^{-1}$ and $g^{-1}.$ Compute \[f(g^{-1}(f^{-1}(f^{-1}(g(f(19)))))).\]

Guest Nov 16, 2014

Best Answer 

 #1
avatar+19597 
+5

$$\small{\text{
$
\begin{array}{rcl}
f(x)=x+2 \\
f^{-1}(x) &=& ? \\
y & =& x+2 \quad | \quad x\leftrightarrow y \\
x & = & y+2 \\
y & = & x-2 \\
f^{-1}(x) & = & x-2 \\
\hline
\\
g(x)=\dfrac{x}{3} \\ \\
g^{-1}(x) &=& ? \\
y & =& \dfrac{x}{3} \quad | \quad x\leftrightarrow y \\ \\
x & = & \dfrac{y}{3} \\ \\
y & = & 3x \\
g^{-1}(x) & = & 3x \\
\hline
\end{array}
$
}}$$

$$\small{\text{
$
\begin{array}{rcccl}
f(19) & = & 19 + 2 & = & 21 \\
g(21) & = & \frac{21}{3} & = & 7 \\
f^{-1}(7) & = & 7-2 & = & 5 \\
f^{-1}(5) & = & 5-2 & = & 3 \\
g^{-1}(3) & = & 3*3 & = & 9 \\
f(9) & = & 9 + 2 & = & 11 \\
\end{array}
$
}}$$

$$f(g^{-1}(f^{-1}(f^{-1}(g(f(19)))))) = 11$$

heureka  Nov 17, 2014
 #1
avatar+19597 
+5
Best Answer

$$\small{\text{
$
\begin{array}{rcl}
f(x)=x+2 \\
f^{-1}(x) &=& ? \\
y & =& x+2 \quad | \quad x\leftrightarrow y \\
x & = & y+2 \\
y & = & x-2 \\
f^{-1}(x) & = & x-2 \\
\hline
\\
g(x)=\dfrac{x}{3} \\ \\
g^{-1}(x) &=& ? \\
y & =& \dfrac{x}{3} \quad | \quad x\leftrightarrow y \\ \\
x & = & \dfrac{y}{3} \\ \\
y & = & 3x \\
g^{-1}(x) & = & 3x \\
\hline
\end{array}
$
}}$$

$$\small{\text{
$
\begin{array}{rcccl}
f(19) & = & 19 + 2 & = & 21 \\
g(21) & = & \frac{21}{3} & = & 7 \\
f^{-1}(7) & = & 7-2 & = & 5 \\
f^{-1}(5) & = & 5-2 & = & 3 \\
g^{-1}(3) & = & 3*3 & = & 9 \\
f(9) & = & 9 + 2 & = & 11 \\
\end{array}
$
}}$$

$$f(g^{-1}(f^{-1}(f^{-1}(g(f(19)))))) = 11$$

heureka  Nov 17, 2014

13 Online Users

New Privacy Policy

We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive information about your use of our website.
For more information: our cookie policy and privacy policy.